Perceptions on mental health of teachers at a public school on the west border of Rio Grande do Sul (Research, Society and Development, 2020)
This study seeks to reflect and discuss about the perception that teachers have about the concept of mental health and their own mental health condition. It is an exploratory descriptive study developed in a state high school, in a municipality on the western border of the State of Rio Grande do Sul. A questionnaire was applied containing open and closed questions, with guiding questions. Data analysis was based on content analysis, with the breakdown of responses into categories. 33 female teachers and 7 teachers participated in the study, totaling 40 individuals. Through the analysis of the data it was possible to notice that the teachers of the school present a superficial understanding of the concept of mental health, relating to behavioral and attitudinal actions. They visualize their mental health status as impaired, bringing stress and exhaustion as the main reasons for such a situation, in addition to visualizing influences of routine and work environment, such as professional devaluation and interpersonal relationships as factors of influence on their health status. mental. Such results help a better understanding of the theme among the population addressed, contributing to the development of more effective strategies for improvement and promotion of mental health.